2023
DOI: 10.1182/blood.2022016943
|View full text |Cite
|
Sign up to set email alerts
|

BTG1 inactivation drives lymphomagenesis and promotes lymphoma dissemination through activation of BCAR1

Abstract: Understanding the functional role of mutated genes in cancer is required to translate the findings of cancer genomics into therapeutic improvement. BTG1 is recurrently mutated in the MCD/C5 subtype of diffuse large B cell lymphoma (DLBCL), which is associated with extranodal dissemination. There, we provide evidence that Btg1 knock-out accelerates the development of a lethal lymphoproliferative disease driven by Bcl2 overexpression. We further show that the scaffolding protein BCAR1 is a BTG1 partner. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…No reports have examined the function of BTG2 in malignant lymphoma pathogenesis, although BTG2 mutations are frequently found in several lymphomas, such as DLBCL 46 and FL, 47 and this mutation was reported as a poor prognostic factor in primary testicular DLBCL 48 . Recently, some studies have demonstrated that functional disruption of BTG1, which belongs to the APRO family and is frequently mutated in GCB‐DLBCL and FL, drives the formation of aggressive BCLs 49,50 . BTG1 acts as an immune gatekeeper in GC B cells and mutant BTG1 promotes aggressive BCLs in humans and mice 49 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No reports have examined the function of BTG2 in malignant lymphoma pathogenesis, although BTG2 mutations are frequently found in several lymphomas, such as DLBCL 46 and FL, 47 and this mutation was reported as a poor prognostic factor in primary testicular DLBCL 48 . Recently, some studies have demonstrated that functional disruption of BTG1, which belongs to the APRO family and is frequently mutated in GCB‐DLBCL and FL, drives the formation of aggressive BCLs 49,50 . BTG1 acts as an immune gatekeeper in GC B cells and mutant BTG1 promotes aggressive BCLs in humans and mice 49 .…”
Section: Discussionmentioning
confidence: 99%
“…BTG1 acts as an immune gatekeeper in GC B cells and mutant BTG1 promotes aggressive BCLs in humans and mice 49 . BTG1 inactivation also drives lymphomagenesis throughout the interaction with the scaffold protein BCAR1 50 . Regarding the mechanism by which BTG2 regulates BCR signaling, PRMT1, which interacts with BTG2 and catalyzes asymmetric dimethylation of arginine‐residues localized within glycine arginine‐rich regions, has been previously reported to suppress BCR signaling through CD79A R198 methylation just below the ITAM region 44,51,52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Inactivating BTG1 mutations promote lymphomagenesis by dysregulating several key processes leading to enhanced oncogenic fitness and cell migration. 48,49 The mutations we identified in CARD11 were located within the coiled-coil domain of scaffold protein CARD11 (K215Q and L341V), a region that is often mutated in DLBCL. 50 CARD11 is a crucial adaptor protein acting downstream of antigen receptor signaling, regulating signaling pathways involved in immune function and cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…For example, versatile gain-of-function (ORF-overexpression based) and loss-of-function (RNAi or CRISPR/CAS9) screenings have blown the way of functional protein investigation. Though our Cell-PCA screen performed an appropriate readout in different studies (Delage et al, 2023; Jia et al, 2023) , even leaky ORF expression existing in the cold CC-ORF cell library, some optimizations are still needed, for not only a known-issue patch, but also aiming to keep Cell-PCA a comparable method alongside of ever-changing technical progress.…”
Section: Introductionmentioning
confidence: 99%